Implementation of a Correspondence Inventory System at the Communication and Informatics Office in Takengon Central Aceh - Hayati, T. Rahmatul (PT. Technology Laboratories Indonesia (TechnoLabs), 2026)
The current mail administration system at Diskominfo still on manual processes, which are prone to errors, time-consuming, and difficult to access. Therefore, this study proposes the implementation of a system based on google Workspace, which includes the use of Google Forms for collecting incoming and outgoing mail data, Google sheets for storing and managing data, and Google sites for displaying reports in a transparent and structured manner. The aim of this proposed system is to enhance the efficiency of mail administration processes, reduce the risk of errors, and facilitate information access for relevant parties. The method used in this study is system desigh using a cloud-based modal, where data can be accessed anything and anywhere with an internet connection. Yhe implementation and increase work productivity. The results show that the new system is more efficient, easier to eperate, and more secure in terms of data storange and distribution.